Book Review: The fate of Greenland: lessons from abrupt climate change, by Philip Conkling, Richard Alley, Wallace Broecker and George Denton, The MIT Press, Cambridge, MA, 2011, 216 pp, ISBN 978-0-262015646 - Fairweather, Helen (Australasian Journal of Environmental Management, 2013)
No abstract available.